2016
DOI: 10.1530/eje-15-0946
|View full text |Cite
|
Sign up to set email alerts
|

Association of mitotane with chylomicrons and serum lipoproteins: practical implications for treatment of adrenocortical carcinoma

Abstract: Mitotane absorption involves chylomicron binding. High concentrations of o,p'-DDA and o,p'-DDE in chyle suggest intestinal mitotane metabolism. In serum, the majority of mitotane is bound to lipoproteins. In vitro, lipoprotein binding inhibits activity of mitotane suggesting that lipoprotein-free mitotane is the therapeutically active fraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 45 publications
5
35
1
Order By: Relevance
“…For the monolayer culture, there was no significant difference in cytotoxicity between MT in EtOH and MT in micelles ( p > 0.05) upon 24 h incubation ( Figure 5 a). The IC 50,24h were 15 and 19 µ m for MT in EtOH and micelles, respectively, which corresponds well with values found in the literature (IC 50,24h = 15 µ m . The cell viability was less than 3% at 50 µ m MT concentration (either in EtOH or micelles) consistent with the previous reports by Silveira et al and others .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…For the monolayer culture, there was no significant difference in cytotoxicity between MT in EtOH and MT in micelles ( p > 0.05) upon 24 h incubation ( Figure 5 a). The IC 50,24h were 15 and 19 µ m for MT in EtOH and micelles, respectively, which corresponds well with values found in the literature (IC 50,24h = 15 µ m . The cell viability was less than 3% at 50 µ m MT concentration (either in EtOH or micelles) consistent with the previous reports by Silveira et al and others .…”
Section: Resultssupporting
confidence: 91%
“…Even at high cumulative doses of 4 to 6 g per day for a consecutive of 3 months, more than half of the patients do not achieve targeted plasma concentration . Overall, MT pharmacokinetics exhibit large inter‐individual variability which appears to be due in part due intestinal and/or hepatic metabolism . The inactive metabolite o,p′‐DDA is also found ten times higher in blood than the active parent compound MT .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 and Supplementary Tables 5, 6). Prior studies (46,47) suggested that mitotane cytotoxicity may be influenced by cholesterol-bearing lipoproteins such as LDL and HDL. In the presence of artificially low lipoprotein levels (0.005 mg/mL HDL, 0.005 mg/mL LDL), median IC 50 of not only nonresistant but also resistant cells dropped significantly compared to more physiological levels (0.05 mg/mL HDL, 0.05 mg/mL LDL) ( Supplementary Fig.…”
Section: Mitotane-resistant Cells Show Profoundly Altered Intracellulmentioning
confidence: 99%
“…It has been shown that mitotane has a low oral bioavailability (F) of 35-40% (11) and a high volume of distribution, which is likely due to its lipophilic nature and extensive accumulation in adipose tissue (12). The majority of mitotane has been found to be bound to lipoprotein particles in circulation with pharmacological activity limited to the unbound fraction (13,14,15).…”
Section: Introductionmentioning
confidence: 99%